Faktor-Faktor Yang Berhubungan Dengan Persepsi Ibu Terhadap Status Gizi Balita Di Kota Bengkulu - Yance Hidayat; Nuche Marlianto; Mariza Arfianti (Journal Of Midwifery And Nursing Studies, 2021)
Lack of parental care for the nutritional status of toddlers during their growth and development period can have a negative impact in the future. This impact will affect their health and can be the initial cause of the incidence of non-communicable diseases in the future. This research is a cross-sectional study that uses simple random sampling technique in calculating the number of respondents and from the calculations obtained the number of respondents is 488 respondents. This study uses a questionnaire as a research tool in which the data tested using logistic regression as a data analysis model. From the biostatistical test, it is known that the factors associated with maternal perceptions are maternal education (AOR: 3.15; 95%CI: 2.03-4.88; p-value: <0.001), knowledge (AOR: 2.35; 95%CI: 1.38-4.01; p-value: 0.002), rate (AOR: 2.08; 95%CI: 1.32-3.26; p-value: 0.001) and income (AOR: 1.99; 95%CI: 1.29- 3.07; p-value: 0.002). From the results of the study, it can be said that the factors that influence the mother's perception of the nutritional status of children under five are mother's education, knowledge, nutritional status, ethnicity and income.